A Suffragette in America: Reflections on Prisoners, Pickets and Political Change - Sangster, Joan (Labour / Le Travail, 2020)
The article reviews the book, "A Suffragette in America: Reflections on Prisoners, Pickets and Political Change," by E. Sylvia Pankhurst, edited with an introduction by Katherine Connelly,.